2010
DOI: 10.1159/000286347
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Mortality in Elderly Patients on Dialysis

Abstract: Elderly patients are increasingly enrolled in dialysis programs and present a series of special characteristics due to their high morbidity and mortality. Objective:To describe the characteristics of incident dialysis patients aged >75 years, their comorbidities and their admissions, with a view to determining the factors that influence their course and mortality. Patients and Methods: The study included all patients aged >75 years who started dialysis in our center since January 2000. The mean duration of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
3
23
1
3
Order By: Relevance
“…The survival of our patients beyond age 80 is similar or even better in comparison to other single-center studies of recent years [5,8,9]. Single-center data usually show better results than registry data, which represent all patients.…”
Section: Discussionsupporting
confidence: 65%
“…The survival of our patients beyond age 80 is similar or even better in comparison to other single-center studies of recent years [5,8,9]. Single-center data usually show better results than registry data, which represent all patients.…”
Section: Discussionsupporting
confidence: 65%
“…Given the morbidity and mortality associated with infections in HD patients, knowledge of the most optimal dosing scheme for a given antimicrobial is critical for ensuring the highest probability of success (3). For a number of antibiotics, multiple dosing recommendations in HD patients have been published (25).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, more than 300,000 receive thrice-weekly hemodialysis (HD) as their primary mode of kidney replacement therapy. Infections among patients on HD are common and account for nearly 30% of all deaths in this population (2,3). One of the most common pathogens associated with infections in the HD population is methicillin-resistant Staphylococcus aureus (MRSA) (4,5).…”
mentioning
confidence: 99%
“…6,7 It was reported that improved initial clinical status of elderly end-stage renal disease (ESRD) patients and better preparation for dialysis was associated with increased survival. 8 Decreased functional capacity, sensory deficits, cognitive impairment and depression have frequently been found in hemodialysis (HD) patients [9][10][11] but only a few studies used comprehensive geriatric assessment (CGA) to evaluate HD patients.…”
Section: Introductionmentioning
confidence: 99%